Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Determine the inverse of the function f(x) = 3(x - 4)^2 + 5.

Sagot :

f(x) as given has no inverse. We see that, for instance, f(1) = f(7) = 32; that is, two different values of x give the same value of f(x), so f is not one-to-one.

We can however restrict the domain over which f is defined to extract an invertible function. One such choice would be to restrict to the interval x ≥ 4, which I'll demonstrate below.

Recall the definition of function inverse:

f(f^(-1)(x)) = x

Then for this function, we have

3 (f^(-1)(x) - 4)² + 5 = x

3 (f^(-1)(x) - 4)² = x - 5

(f^(-1)(x) - 4)² = (x - 5)/3

√((f^(-1)(x) - 4)²)= √((x - 5)/3)

For all x, √(x²) = |x|. Then √((f^(-1)(x) - 4)²) = |f^(-1)(x) - 4|, but by restricting x ≥ 4, or x - 4 ≥ 0, we have the condition that f^(-1)(x) - 4 ≥ 0, and so by definition (of the absolute value function) the absolute value reduces to the positive case. In short, we end up with

f^(-1)(x) - 4 = √((x - 5)/3)

and hence the inverse

f^(-1)(x) = √((x - 5)/3) + 4